2014
DOI: 10.1007/s40279-014-0267-6
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Vitamin D Inadequacy in Athletes: A Systematic-Review and Meta-Analysis

Abstract: Despite the limitations of the current evidence, the prevalence of vitamin D inadequacy in athletes is prominent. The risk significantly increases in higher latitudes, in winter and early spring seasons, and for indoor sport activities. Regular investigation of vitamin D status using reliable assays and supplementation is essential to ensure healthy athletes. The prevalence of injuries in athletes is notable but its association with vitamin D status is unclear. A well-designed longitudinal study is needed to a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

24
184
1
9

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 195 publications
(218 citation statements)
references
References 49 publications
24
184
1
9
Order By: Relevance
“…A surprisingly high prevalence of vitamin D insufficiency has been recently reported worldwide (Table 1) regardless of their insolation [20][21][22][23]. In Canada, 30-50 % of children and adults are vitamin D deficient and need vitamin D supplementation [24].…”
Section: Vitamin D Deficiencymentioning
confidence: 99%
See 1 more Smart Citation
“…A surprisingly high prevalence of vitamin D insufficiency has been recently reported worldwide (Table 1) regardless of their insolation [20][21][22][23]. In Canada, 30-50 % of children and adults are vitamin D deficient and need vitamin D supplementation [24].…”
Section: Vitamin D Deficiencymentioning
confidence: 99%
“…Indeed, athletes may be more vulnerable to vitamin D deficiency than age-matched non-athletes even in regions with insolation. A recent meta-analysis pooling 23 studies composed of 2313 athletes found that 56 % of athletes had inadequate vitamin D [23]. In addition, a sizeable number of athletes do not meet the US dietary reference intake for vitamin D in addition to their inadequate endogenous synthesis when they train indoors [27].…”
Section: Vitamin D Deficiencymentioning
confidence: 99%
“…1 Despite the importance of vitamin D to musculoskeletal health, vitamin D deficiency and insufficiency are becoming globally prevalent. [2][3][4] It is estimated that worldwide there are 1 billion people who are vitamin D deficient or insufficient, 5,6 including 3.3 million Canadians 7 and 250 million Americans who are vitamin D deficient. 8 At the cellular level, vitamin D is involved in every stage of the complex process of fracture healing through its effects on inflammatory cells, cytokines, growth factors, osteoblasts, osteoclasts, and through its effect on the process of mineralization.…”
Section: Introductionmentioning
confidence: 99%
“…Patient education regarding proper diet, bone mineral density (BMD), and adequate levels of vitamin D should be emphasized. 20,21 Additional evaluation is important in women who are athletes with menstrual irregularities and eating disorders due to the increased risk of stress fractures. 22 Lower BMD delays recovery from these injuries and increases the risk of future osteoporotic fractures.…”
Section: Bone Healthmentioning
confidence: 99%